A physiological explanation for the canopy nitrogen requirement of winter wheat - Critchley, Claire Siân (2001)
Nitrogen (N) fertiliser is one of the most important agronomic inputs and yet the application recommendations for winter wheat (Triticum aestivum L.) still remain imprecise. This increases costs both to the wheat grower and to the environment. An understanding of the canopy nitrogen requirement (CNR) is required before any improvements in fertiliser recommendations can be made. The CNR is defined here as the minimum amount of N required to produce and maintain a canopy and be efficient in light capture and conversion. This thesis aimed to provide a physiological explanation for this requirement in winter wheat, based on canopy structure and radiation geometry, to test the hypothesis that CNR can be predicted from canopy architecture.